Editoria PPP 16(4) - Pimentel, Alessandra; Baroni, Daiana Paula; dos Santos, Gleidson Jordan; Alvarenga Filho, José Rodrigues de; Queiroz e Melo, Maria de Fatima Aranha de; Henriques, Victor Freitas; Santos, Joelma Cristina (Revista Pesquisas e Práticas Psicossociais, 2022)
.